2020
DOI: 10.22271/oral.2020.v6.i4d.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermo-cycling on microhardness of CAD-CAM provisional materials

Abstract: Temporary restorations are an important stage of fixed prosthetic treatment in the period until the final restoration is made and the most appropriate provisional material with CAD-CAM technology used today should be researched. The aim of this study was to investigate the effect of thermo-cycling on micro hardness of CAD-CAM Provisional materials. Materials and methods: Three types of provisional restorative materials produced for CAD-CAM systems were examined: Vita CAD Temp (Vita Zahnfabrik, Germany), Telio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Similar to previous reports, 23 28 in the present study, CAD-CAM provisional restorative materials are statistically affected by thermocycling 28 and bis-acryl resin composite materials exhibited superior microhardness over traditional methyl methacrylate resins. 29 In another study, Digholkar et al 30 reported the highest microhardness of provisionals produced by 3D printing over CAD-CAM PMMA milling and conventional method.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous reports, 23 28 in the present study, CAD-CAM provisional restorative materials are statistically affected by thermocycling 28 and bis-acryl resin composite materials exhibited superior microhardness over traditional methyl methacrylate resins. 29 In another study, Digholkar et al 30 reported the highest microhardness of provisionals produced by 3D printing over CAD-CAM PMMA milling and conventional method.…”
Section: Discussionsupporting
confidence: 89%
“…As the combined use of chewing simulation and thermocycling is a well-documented method to mimic clinical situations [ 30 ], 10/20 FDPs were exposed to thermal and mechanical loading. Based on the assumption that a chewing simulation with 1.2 million cycles corresponds to a wearing time of approximately five years [ 31 ], a clinical use of two years for a long-term temporary restoration was simulated in this study.…”
Section: Materials Experimental Procedures and Methodsmentioning
confidence: 99%